Pengaruh Disiplin Kerja Terhadap Produktivitas Kerja Pegawai Pada Puskesmas Malaimsimsa Kota Sorong - Yudirman, Yudirman; Samallo, Oktagrian; Zaman, Melan (Universitas Gajah Putih, 2023)
Productivity is one of the important things that every organization should pay attention to. Low work productivity will affect the quality of the organization, because work productivity is used to measure the value of resources owned by the organization in a job. This study aims to determine the influence. Work discipline on Work Productivity at the Malaimsimsa Health Center in Sorong City. The research method used was a quantitative method with 50 employees. The data collection technique used is a data questionnaire. The results showed that discipline had no effect on work productivity.